Factor model for the Singapore stock market. - Bertram Rodrigo F. Sarmago. (2008)
Factor models provide a good understanding between asset returns and a number of factors. In Singapore, a number of factors are expected to influence the equity market returns. Using this context, we identified global and regional market factors with local economic factors to explain the return variation of the Singapore equities market.